2016
DOI: 10.1111/jfq.12190
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Salad Dressing Emulsions Using Lentil, Chickpea and Pea Protein Isolates: A Response Surface Methodology Study

Abstract: The effect of pulse protein, egg yolk and oil contents on the physical properties (i.e., static and dynamic rheological behavior, texture) of lentil-, pea-and chickpea-supplemented salad dressings was studied using a three-factor central composite design (CCD). Multiple regression equations were developed to describe the effects of the independent variables on several response variables. In general, an increase in oil and emulsifier (pulse protein or egg yolk) contents modified the rheological and textural pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…This flow behavior characteristic is the typical flow behavior of salad dressing. Many previous studies have demonstrated shear thinning flow characteristics of salad dressing (Fernandez, Palazolo, Bosisio, Martínez, & Wagner, ; Ma, Boye, & Simpson, ).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This flow behavior characteristic is the typical flow behavior of salad dressing. Many previous studies have demonstrated shear thinning flow characteristics of salad dressing (Fernandez, Palazolo, Bosisio, Martínez, & Wagner, ; Ma, Boye, & Simpson, ).…”
Section: Resultsmentioning
confidence: 94%
“…This flow behavior characteristic is the typical flow behavior of salad dressing. Many previous studies have demonstrated shear thinning flow characteristics of salad dressing(Fernandez, Palazolo, Bosisio, Martínez, & Wagner, 2012;Ma, Boye, & Simpson, 2016).The consistency index (K) and n values of the samples were calculated by using the Power Law model. The K and n values of the 27 different points are shown in Table 1.…”
mentioning
confidence: 99%
“…Indeed, Bird et al (2017) observed reduced crumb hardness after incorporating chickpea boiling water into a bread formulation and when compared to the breads obtained by using xanthan gum. Ma et al (2016) also suggested that pulse-derived proteins were promising and valuable replacements of egg proteins in emulsion-type food products. The authors of that study optimised a salad dressing formulation using RSM and obtained products with textural properties that were comparable to those of the control.…”
Section: Comparison Between Vegan and Egg-based Meringues And Mayonnamentioning
confidence: 99%
“…The rheological analysis of salad dressings has been investigated in literature because an adequate formulation, the process conditions, and quality properties, sensory attributes, shelf life, and microstructure are important for the choice of salad dressing (Maani, Alimi, Shokoohi, & Fazeli, 2016). Several researches have been conducted on steady and dynamic rheological properties of the salad dressing type emulsions (Li et al., 2019; Ma et al., 2013; Ma, Boye, & Simpson, 2016; Mandala, Savvas, & Kostaropoulos, 2004). Limited research has been found in literature 3‐ITT rheological properties of the salad dressing (Akcicek & Karasu, 2018), and no research has been carried out to characterize 3‐ITT and other rheological behavior of salad dressings stabilized by cold‐press flaxseed oil by‐products.…”
Section: Introductionmentioning
confidence: 99%